The curvilinear effect of perceived overqualification on constructive voice: The moderating role of leader consultation and the mediating role of work engagement - Duan, Jinyun; Xia, Ying; Xu, Yue; Wu, Chia‐Huei (Human Resource Management, 2022)
AbstractDrawing on the social cognitive theory of self‐regulation, we proposed a model considering an inverted U‐shaped relationship between perceived overqualification and constructive voice. We reasoned from the theory that this curvilinear effect would be moderated by leader consultation, which could intensify the upward curvilinear trend and neutralize the downward curvilinear trend, and be mediated by work engagement. We conducted two studies to test our model. In Study 1, based on a three‐wave time‐lagged sample of 293 employees and 120 supervisors, we found an inverted U‐shaped relationship between perceived overqualification and constructive voice, which was moderated by leader consultation. In Study 2, we examined the proposed mediated moderation model using a sample of 231 matched leader–subordinate dyads. We found that, at lower levels, perceived overqualification has a positive association with constructive voice, which is mediated by work engagement, especially at higher leader consultation. At higher levels, perceived overqualification has a negative association with work engagement and thus constructive voice, especially at lower levels of leader consultation. The implications of our research are discussed.